2002
DOI: 10.1093/ije/31.6.1235
|View full text |Cite
|
Sign up to set email alerts
|

Fetal origins of adult disease: strength of effects and biological basis

Abstract: Coronary heart disease and type 2 diabetes may originate through two widespread biological phenomena-developmental plasticity and compensatory growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
1,159
4
52

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,744 publications
(1,235 citation statements)
references
References 28 publications
20
1,159
4
52
Order By: Relevance
“…For many aspects of the metabolic syndrome, risk is greatest in those born small who subsequently gain the most weight (Bavdekar et al 1999;Adair & Cole, 2002;Barker et al 2002). Recent studies have begun to distinguish the contributions of different periods of postnatal weight gain to later phenotype and disease risk , but the generalisability of such findings remains unclear.…”
Section: Postnatal Growth and Subsequent Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many aspects of the metabolic syndrome, risk is greatest in those born small who subsequently gain the most weight (Bavdekar et al 1999;Adair & Cole, 2002;Barker et al 2002). Recent studies have begun to distinguish the contributions of different periods of postnatal weight gain to later phenotype and disease risk , but the generalisability of such findings remains unclear.…”
Section: Postnatal Growth and Subsequent Body Compositionmentioning
confidence: 99%
“…In many cases the strongest association between birth weight and later outcome is found when a statistical adjustment for adult size is incorporated (Barker et al 2002). This issue has more than one implication.…”
mentioning
confidence: 99%
“…In other cases, integration of signals received from maternal hormones may trigger epigenetic modifications that alter long-term phenotypic development by modulating RNA coregulatory networks 96 . Low birth weight, for example, has been shown to correlate with lifetime risk of cardiovascular disease and diabetes mellitus, presumably by resetting developmental programs 97 . Furthermore, the recent demonstration that plasma RNA is quite stable 98 raises the question of whether coRNAs secreted by various somatic tissues are used to transmit information from mother to fetus.…”
Section: Replication Of Ribotypesmentioning
confidence: 99%
“…This adverse environment may change gene expression, leading to physiological phenotypes associated with morbidity and mortality. 1,2 Newborns with a low birth weight have increased risk for perinatal as well as adult morbidity and mortality, 2 whereas newborns with a high birth weight are at increased risk for several complications, such as shoulder dystocia, operative delivery, and birth canal lacerations. 3 High birth weight is also associated with increased risk during adulthood of type 2 diabetes and some types of cancer (for example, endometrial, breast, or prostate).…”
Section: Introductionmentioning
confidence: 99%
“…3 High birth weight is also associated with increased risk during adulthood of type 2 diabetes and some types of cancer (for example, endometrial, breast, or prostate). 1,2,4,5 The effect of exercise training during the course of pregnancy on the newborn's birth weight is unclear. Two meta-analyses reported that exercise during pregnancy normally does not affect birth weight, 6,7 but a more recent Cochrane meta-analysis concluded that the available data are insufficient to infer important risks or benefits for the mother or infant.…”
Section: Introductionmentioning
confidence: 99%